«ДУХОВНЫЙ ОПЫТ»: МОДУСЫ РЕПРЕЗЕНТАЦИЙ В ПРЕДСТАВЛЕНИЯХ КУЛЬТУР - Компаниец, Л. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Статья посвящена осмыслению «духовного опыта» как явления религиозной культуры (на примере традиционной культуры). Проводится анализ специфики «мистического опыта», выявление его видовых присутствий в социокультурных реалиях прошлого. Презентуются взгляды и типологии «духовного опыта» более поздних времён. Автор приходит к заключению, что «мистический опыт» присутствовал в тех или иных формах на протяжении всей истории культур. Его идеи составляли основу религиозных представлений последующих веков. Компанієць Л.В. «Духовний досвід»: модуси репрезентацій в уявленні культур. Статтю при- свячена осмисленню «духовного досвіду» як явища релігійної культури (на прикладі традиційної культу- ри). Проводиться аналіз специфіки «містичного досвіду», виявлення присутності його видів у соціокультурних реаліях минулого. Презентуються погляди і типології «духовного досвіду» більш пізніх часів. Автор приходить до висновку, що «містичний досвід» присутній в тих чи інших формах протягом всієї історії культур. Його ідеї становили основу релігійних уявлень наступних століть. Ключові слова: містика, духовний досвід, стан, феномен. Kompaniec l.V. «Spiritual experience»: moduses of reprezentation in presentation of cultures. The article is devoted to understanding the mystery of religious culture as a phenomenon, and, in particular, the "spiritual experience" as a form of mystical dimension of human existence on the plane of matter (for example, the traditional culture). The paper deals with the basic understanding of the concepts "mysticism", "spirituality". They singled out the basic meanings of space, performed accents in their use. The author proceeds from the many existing explications that reveal different aspects of the concept of "mysticism", realized at different levels of culture and presents his understanding of mysticism as a social and cultural phenomenon, a universal attribute of religious phenomena. In the course of research conducted intelligence extraction and examination forms of the existence of "spiritual experience" in the context of a retrospective, in the light of various mystical practices, the example of the ancient rite of passage. Found that the "spiritual experience" in the measurements of the traditional society is a fairly widely permeates the sacred space of primitive culture, people have been through it opens the way to the religion, history, essence, the mysteries of the world and life. As a result of the development through a "spiritual experience" of cultural traditions of his family, the tribe, the old man could expect to fully live within their community. Keywords: mystic, spiritual experiences, status, phenomenon.